The Evolving Role of the Professional Support Lawyer. (2018) - Bateman, Julia; Russell, Hélène; Shenkman, Evan J; Troostwyk, Lucinda; Battersby, Karen; Hall, Lucy; Hamilton, Amanda; Harman Clark, Clare; Hart, Catherine; Hogan, Ailish; Lang, Katherine; Pigott, Charles
No abstract available